ALIROCUMAB : MECHANISM OF ACTION, PHARMACOKINETICS, SAFETY, AND CLINICAL OUTCOMES - Medina, Farah; -, Sumarno (Brawijaya University, 2019)
Hyperlipidemia is an established risk factor for developing cardiovascular disease (CVD). The latest guideline on lipid management emphasize treatment with 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors (statins) at doses proven to reduce CVD events. Â However, some of statin-treated patients have persistently elevated cardiovascular risk due to inadequate lowering of low density lipoprotein cholesterol (LDL-C) levels. In addition, adverse effects of statins may limit their tolerability and therefore the ability to attain effective doses in some patients. A new class of drugs that inhibit proprotein convertase subtilisin-kexin type 9 (PCSK9) has been developed to treat hyperlipidemia. Â PCSK9 inhibitors are monoclonal antibodies for proprotein convertase-subtilicin/kexin type 9 which significantly reduces the concentration of LDL-C in vivo by inhibiting the degradation of LDL receptors in hepatocytes. The introduction of the PCSK9 inhibitor was heralded a new era of intensive LDL-C reductions with LDL-C concentrations lowered below the rate that once thought possible with conventional treatments such as statins. On July 24, 2015, the United States Food and Drug Administration (FDA) approved Alirocumab, the first converged proprotein of the Subtilisin Kexin 9 (PCSK9) inhibitor. This review discusses the mechanisms of action, pharmacokinetics, safety and clinical outcomes of the Alirocumab.